2018
DOI: 10.1002/clc.23086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adiposity indices in relation to prehypertension by age and gender: A community‐based survey in Henan, China

Abstract: Background To compare the efficiency of bioelectrical indices (visceral fat index [VFI], percentage body fat [PBF]) and anthropometric indices (body mass index, waist circumference, waist‐to‐height ratio, a body shape index ) in the relation to prehypertension (120‐139/80‐89 mm Hg) among the Chinese population. Methods Using stratified multistage random sampling method, a general population‐based sample of 11 175 adults in Henan province were selected from 2013 to 2015. The individuals were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Previous studies reported that obesity was closely related with hypertension, which is consistent with our findings [5,10,20]. We found that all six adiposity indices were positively and significantly associated with hypertension and the ORs for hypertension increased monotonically with increasing levels of six adiposity indices.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that obesity was closely related with hypertension, which is consistent with our findings [5,10,20]. We found that all six adiposity indices were positively and significantly associated with hypertension and the ORs for hypertension increased monotonically with increasing levels of six adiposity indices.…”
Section: Discussionsupporting
confidence: 92%
“…9 Besides, body fat percentage can also be a marker which is useful for identifying the risk of prehypertension in young adults. 28…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different markers of adiposity have been associated with hypertension in the general population of different geographical areas, both in adults and children, whether male or female. [7][8][9][10][11][12][13][14] One of the first key questions that may arise when dealing with this issue is the role of the different markers of obesity, mainly as predictors. Dozens of papers on obesity use different markers to assess obesity, but it is not clear which one is the most reliable.…”
mentioning
confidence: 99%
“…Several studies have explored the relationship of hypertension with obesity in a cross‐sectional way. Thus, different markers of adiposity have been associated with hypertension in the general population of different geographical areas, both in adults and children, whether male or female …”
mentioning
confidence: 99%
See 1 more Smart Citation